2020
DOI: 10.3390/ani10040699
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Aggression, Dominance and the Impacts of Visitor Interaction on Galápagos Tortoises (Chelonoidis nigra) in a Zoo Setting

Abstract: Ensuring high levels of welfare is imperative for modern zoos, but such organisations must also engage visitors in order to successfully spread awareness and raise conservation funds. It is therefore important to understand the responses of animals to visitor interaction to optimise welfare. Often, the opportunity to interact with humans may be enriching for animals, but in other contexts, this interaction may have negative welfare effects. We observed captive female Galápagos giant tortoises (Chelonoidis nigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Although some behaviors (e.g., stereotypic behavior, aggression) are often associated with negative animal welfare, and other behaviors (e.g., play, affiliative social interactions) are sometimes associated with positive welfare [ 40 , 67 ], Sherwen and Hemsworth [ 21 ] stressed that many behaviors may not have clear associations with welfare status, and behavioral changes do not always indicate that the change is negative [ 68 ]. We acknowledge that an animal’s behavioral response (for example, decreasing rest behavior) does not necessarily indicate a particular emotional response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some behaviors (e.g., stereotypic behavior, aggression) are often associated with negative animal welfare, and other behaviors (e.g., play, affiliative social interactions) are sometimes associated with positive welfare [ 40 , 67 ], Sherwen and Hemsworth [ 21 ] stressed that many behaviors may not have clear associations with welfare status, and behavioral changes do not always indicate that the change is negative [ 68 ]. We acknowledge that an animal’s behavioral response (for example, decreasing rest behavior) does not necessarily indicate a particular emotional response.…”
Section: Discussionmentioning
confidence: 99%
“…minor [ 34 ]), greater rheas ( Rhea americana [ 35 ]), slender-tailed meerkats ( Suricata suricatta [ 36 ]), and African penguins ( Spheniscus demersus [ 37 ]). However, zoo visitors impacted aggressive, huddling, and avoidance behaviors [ 38 ], as well as location within the exhibit area [ 39 ], in little penguins ( Eudyptula minor ), aggression and activity levels in female Galápagos giant tortoise ( Chelonoidis nigra [ 40 ]), and vigilance in koalas ( Phascolarctos cinereus [ 41 ]). Furthermore, studies have found variable patterns related to inactive behavior: from resting more when visitor abundance was low [ 25 ] to resting more when visitor abundance was high [ 42 ], to no change in resting behavior [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the visitor effect, only one study has been conducted including a reptilian species. Freeland et al (2020) looked at the behavior of Galapagos tortoise (Chelonoidis nigra) when humans entered their exhibit [29]. The results show that tortoise aggression was greater on days where zoo visitors, accompanied by zoo employees, entered the enclosure and interacted with the tortoises (including physical contact) compared to days with either normal husbandry staff presence or days that included a veterinary staff visit [29].…”
Section: Introductionmentioning
confidence: 99%
“…Freeland et al (2020) looked at the behavior of Galapagos tortoise (Chelonoidis nigra) when humans entered their exhibit [29]. The results show that tortoise aggression was greater on days where zoo visitors, accompanied by zoo employees, entered the enclosure and interacted with the tortoises (including physical contact) compared to days with either normal husbandry staff presence or days that included a veterinary staff visit [29]. This singular study, while beneficial as an initial investigation on the potential relationships between visitors and reptilian behavior, illustrates the need for further study to understand how visitor presence affects animal behavior across diverse taxa.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been increased research focus on identifying behaviours that may be indicative of welfare state in reptiles [21][22][23][24][25][26][27][28][29][30]. However, there remains a dearth of primary studies exploring reptile behaviours, their relation to affective state, and how husbandry practices may modify expression of these behaviours.…”
Section: Introductionmentioning
confidence: 99%